Tongling Performing Arts As The Identity Of The Wonomulyo Village - Genilangit - Evie Destiana; Rugaya Meis Andhiarini; Agus Salim (Universitas Muhammadiyah Sidoarjo, 2021)
The Wonomulyo village is one of the most potential in the Genilangit village of any other village. As an act of gratitude for the people of the Wonomulyo village - Genilangit of the vast natural resources of this village, so in 1994 one of the Wonomulyo community decided to create an art musical using bamboo Musical Instruments The art of the Tongling performance stands for both Kentongan and Suling (flute), which are important instruments of the Tongling show. Not a part of the ritual, but merely an amusement for the Wonomulyo village folk during special days, such as the harvest, the feasting, the welcome, and so on. Tongling performance art is the only indigenous art of the Wonomulyo village performance, and it is the trademark, identity, and pride of citizens that to this day have grown with the age, without dismissing the true identity of these performance instruments.